Latin American Integration Route and migrants in the state of Mato Grosso do Sul: a pre-implementation overview - Bianco, Matheus Ibelli (2023)
The Latin American Integration Route (RILA) is a road corridor under implementation that will link the transport infrastructure of Mato Grosso do Sul (MS) to the ports of Northern Chile, passing through Paraguay and Argentina. This project has already resulted in intense socioeconomic transformations. This research aims to offer an overview of migrants in MS and the current governance on this agenda. The hypothesis is that the completion of this international road corridor has positive and negative impacts on the situation of migrants. After the analysis, we appointed that MS has public policies aimed at migration that encompass areas of access to rights and governance. In addition, to having good practices that help migrants access information, the State, through the Fundação do Trabalho, disseminates and assists in job vacancies for these individuals. However, it is fundamental to keep improving these policies through transversality and cooperation between government sectors. Therefore, continuous improvement in the training of civil servants, alliances with the private sector to make jobs available, and policies for welcoming people with education, language courses, and access to rights are essential.